The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/3296285
|View full text |Cite
|
Sign up to set email alerts
|

Choice Behavior of the Elderly Regarding Street-Crossing Facility

Abstract: This study aims to understand the street-crossing-facility choice behavior of the elderly. The footbridges were classified into three types with different levels of convenience. On the other hand, the safety of the crosswalk was assumed to be highly related to the remaining time of pedestrian green light. An adaptive SP survey was designed to collect choice data from individuals aged 60 years or above, and a multilevel logistic model was developed to analyze the behavior data. The results indicated that conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“… Wei et al (2018) showed participants a sequence of videos and asked them to choose whether they would use a crosswalk or a crossing bridge ( Wei et al, 2018 ). The crosswalk included a pedestrian countdown device and the amount of time remaining was manipulated along with the accessibility of the crossing bridge.…”
Section: Summary Of Papers and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Wei et al (2018) showed participants a sequence of videos and asked them to choose whether they would use a crosswalk or a crossing bridge ( Wei et al, 2018 ). The crosswalk included a pedestrian countdown device and the amount of time remaining was manipulated along with the accessibility of the crossing bridge.…”
Section: Summary Of Papers and Discussionmentioning
confidence: 99%
“…However, when the speed limit was 70 km/hr, 84% of pedestrians used the overpass ( Alver & Onelcin, 2018 ). Therefore, it is possible that the presence of the signalized crosswalk in the Wei et al (2018) study made the overpass less appealing due to an apparently “safe” method of crossing.…”
Section: Summary Of Papers and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an aging baby boomer population, elderly mobility is becoming an increasingly important social issue, which has aroused great interest in the research community. In recent years, researchers have studied the issue of elderly mobility from various perspectives, including public transit accessibility [28,29], pedestrian environment [30,31], driving behaviors [32,33], and crossing road intersections [34,35], among many others. Some of these studies have also reported many beneficial findings on the differences between elderly users in the different parts of the world.…”
Section: Introductionmentioning
confidence: 99%